2016
DOI: 10.1016/j.apcatb.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic removal of patent blue V dye on Au-TiO 2 and Pt-TiO 2 catalysts

Abstract: In this work it was studied the efficiency of a photocatalytic process for the removal of Patent blue V. This dye is very difficult to remove by conventional treatments such as adsorption or coagulation therefore the photocatalytic process is a very interesting alternative for the removal this dye mainly because it does not require expensive oxidants and it can be carried out at mild temperatures and pressures. In this work it was tested the efficiency of Au-TiO 2 and Pt-TiO 2 photocatalysts in the Patent blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(59 citation statements)
references
References 28 publications
(32 reference statements)
3
51
0
3
Order By: Relevance
“…and nonmental (N, S, I, etc.) doping, artificial crystal structure modification, and carbonaceous nanomaterial compositing (carbon nanotubes, graphene, and fullerenes) [4][5][6][7][8][9][10]. Nevertheless, the visible-light energy conversion remains insufficient due to little solar light absorption and many carrier-recombination centers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…and nonmental (N, S, I, etc.) doping, artificial crystal structure modification, and carbonaceous nanomaterial compositing (carbon nanotubes, graphene, and fullerenes) [4][5][6][7][8][9][10]. Nevertheless, the visible-light energy conversion remains insufficient due to little solar light absorption and many carrier-recombination centers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the high charge recombination efficiency of TiO 2 also lead to a low quantum yield and a low photocatalytic efficiency, which greatly limits the actual application . Therefore, cation doping, anion doping, semiconductor combination and noble metal modification are often used to enhance the photocatalytic activity of TiO 2 . For the former several methods, the activity enhancement still remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…For the former several methods, the activity enhancement still remains limited. Noble metals such as Au, Ag and Pt can significantly improve the photocatalytic activity of titanium dioxide . However, the high cost is not suitable for wide practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has been recognized as an eco-friendly, less expensive, non-selective and effective alternative in the treatment of effluents. Thus, a number of studies have demonstrated that heterogeneous photocatalysis is a promising approach of Advanced Oxidation Process in the treatment of dyestuffs in the liquid phase [2][3][4][5][6][7][8][9][10][11]. In most of these studies, lab prepared dyes solutions or synthetic wastewater are employed and only a few researchers have conducted studies by using real industrial wastewater samples [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As TiO 2 is the most recognized and employed material in photocatalysis, many efforts have been devoted to improve its effectiveness; thus, noble metal addition [11,18], non-metals doping [19,20], sulfation and fluorination [4,[21][22][23][24][25][26][27][28][29][30] among others have been reported to be suitable alternatives for titania modification. Taking into account that the practical application of TiO 2 is not in the form of dispersions, many studies in this area have been also focused on supported TiO 2 being photolyzed in the presence of a pollutant during a continuous cleaning process [14,16,28,31,32], in these processes the separation of the pollutant from the processed solution at the end of the process it is not necessary.…”
Section: Introductionmentioning
confidence: 99%